The Effect of Deep Oceanic Flushing on Water Properties and Ecosystem Functioning Within Atolls in the British Indian Ocean Territory - Sheehan, Emma V.; Hosegood, Phil; Game, Chloe A.; Attrill, Martin J.; Tickler, David; Wootton, Marianne; Johns, David G.; Meeuwig, Jessica J. (Frontiers in Marine Science, 2019)
Within atolls, deep water channels exert significant control over local hydrodynamic conditions; which are important drivers of planktonic distributions. To examine planktonic responses to oceanography, this study tested the effect of proximity and exposure to deep oceanic flushing through these channels on water properties and planktonic assemblages across four atolls (Diego Garcia, Salomon, Egmont and Peros Banhos) in the British Indian Ocean Territory Marine Reserve. As this is the largest, most isolated and sparsely inhabited atoll complex in the world, it provides the perfect experimental conditions to test the effect of oceanic flushing without confounding factors related to anthropogenic development. Results are discussed in the context of ecosystem functioning. A total of 30 planktonic taxa and 19,539 individuals were identified and counted. Abundance was significantly different between atolls and significantly greater within inner regions in all atolls except southeast Egmont. Planktonic assemblage composition significantly differed between atolls and between inner and outer stations; exhibiting higher similarity between outer stations. Within outer stations of Diego Garcia, Peros Banhos and Egmont, evidence suggesting oceanic flushing of cold, saline and dense water was observed, however a longer time series is required to conclusively demonstrate tidal forcing of this water through deep water channels. Planktonic variability between inner and outer atoll regions demonstrates that broad comparisons between oceanic and lagoon regions fail to capture the complex spatial dynamics and hydrodynamic interactions within atolls. Better comprehension of these distributional patterns is imperative to monitor ecosystem health and functioning, particularly due to increasing global anthropogenic pressures related to climate change. The extensive coral bleaching described in this paper highlights this concern.